Hello, I have the following statement: "Function f.i is non-decreasing as i increases." Does anyone know how I can translate this statement into its Predicate? Thanks!
Follow Math Help Forum on Facebook and Google+
Originally Posted by inthedl Hello, I have the following statement: "Function f.i is non-decreasing as i increases." Does anyone know how I can translate this statement into its Predicate? Thanks! [ x y=====> ~f(x) f(y)]. Which is equivalent to: [ x y=====> f(x)< f(y)]. The predicates here being the inequality symbols
View Tag Cloud